The inter-Islamic competition and the shift in al-Nur party stance towards civil state in Egypt. Issue 1 (1st January 2022) - Magued, Shaimaa
ABSTRACT: Why did al-Nur Salafi party change its stance towards civil state? This study problematizes al-Nur party's discourse on civil state after 25 January and 3 July in emphasis of its ideological shift in different political contexts. Based on the political parties' competition strategies, this study argues that changes in al-Nur party's discourse towards civil state are due to its adoption of different competition strategies vis-à-vis the Muslim Brothers after 25 January and 3 July. Unlike the literature addressing the Islamists' ideological revisions, this paper argues that al-Nur party adopted the issue ownership strategy in order to highlight its ideological specificity vis-à-vis the Brothers' Freedom and Justice Party after 25 January. After 3 July, the party shifted to the wave-riding strategy in compliance with public anti-Islamic feelings in order to take over the political vacuum left after the ban of and the crackdown on the Brothers. By relying on the Critical Discourse Analysis methodology, this study examines the shift in al-Nur party's stance towards civil state in the party's official statements and websites during elections and constitutional referendums after 25 January and 3 July.